(untitled) (American Journal of Islam and Society, 1996)
lqra’! Read! Proclaim! Vowels (tahrik) are the life of the Arabic language; they breathe in its spirit (ruh). Vowels are the dynamic of the word; they regulate its meaning and determine for the verb its active or passive voice. Vowels are nonlocal; "a speech sound produced without occluding, diverting, or constructing the flow of air from the lungs," as opposed to consonants, which do all of the above. Consonants are local. They are the only letters found in Arabic texts, whether handwritten or printed, as in the time of the Jahinyah. Why? We deplore it in the multifold way of our multidisciplinary approach, for we are not living in the very intensive oral tradition of the Jahinyah. Space, time, and communication have demands these days. The Qur’an and the Sunnah, those unsullied fountainheads of Islam, have reached us completely vowelized. This paper is a "complimentary" plea for bringing life (ruh) to the Arabic Islamic texts by marking the short vowels for the sake of those members of the ummah who are in the process of learning it. In his last address, the Prophet evoked "a law which you should preserve and be firmly attached to, a law clear and positive: The Book of God and the Sunnah." At the end of his life, Muhammad (pbuh) had about 30,000 contemporaries who had heard and memorized the Qur’an in whole or part. Several of them could read and write and had committed the Qur’an to writing in part or in toto .... All the revelations written by the Prophet’s scribe were collected and stored in the house of ’A’isha, the Prophet’s wife and daughter of Abu Bakr, the first caliph.’ Twelve years later, ’Uthman, the third caliph, felt the need to compile a standard copy of the Qur’an that would ensure the uniform pronunciation of the Qur’anic text throughout the world. During his rule, Islam had spread far and wide in distant lands inhabited by diverse nationalities. The ...